Effectiveness of Acceptance and Commitment based Therapy on Pain Severity, Fatigue, and Alexithymia in Female Patients with Rheumatic Diseases - Roshandel, Zahra; Ghaffari, Azra; Kazemi, Reza; Nadermohammadi, Mehriar (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this research was determine the effectiveness of acceptance and commitment based therapy on pain severity, fatigue, and alexithymia in female patients with rheumatic diseases. Methods: This study was quasi-experimental with a pretest, posttest and three month follow-up design with a control group. The research population was female patients with rheumatic diseases who referred to the rheumatology clinic of Imam Hossein Hospital of Tehran city in the spring of 2021, which number of 30 people of them after reviewing the inclusion criteria were selected by purposeful sampling method and randomly replaced into two equal groups. The experimental group was trained 8 sessions of 90 minutes (one session per week) with the acceptance and commitment based therapy method and the control group remained on the waiting list for training. Data were collected by revised version of the short-form McGill pain questionnaire (Dworkin et al., 2009), fatigue severity scale (Krupp et al., 1989) and Toronto alexithymia scale (Bagby et al., 1994) and analyzed by methods of repeated measures analysis of variance and bonferroni post hoc test in SPSS-21 software. Results: The results showed that acceptance and commitment based therapy reduced the pain severity, fatigue and alexithymia in female patients with rheumatic diseases and the results remained in the follow-up phase (P<0.001). Conclusion: The results showed the effectiveness of acceptance and commitment based therapy and its persistence in reducing pain severity, fatigue and alexithymia in female patients with rheumatic diseases. Therefore, health professionals and therapists can use acceptance and commitment based therapy along with other therapies methods to improve features, especially pain severity, fatigue and alexithymia.